Investigation of the surgical strategies for unilateral multifocal cystadenolymphomas of the parotid gland - Mantsopoulos, Konstantinos; Koch, Michael; Goncalves, Miguel; Iro, Heinrich (Oral Oncology, 2018)
OBJECTIVES: The aim of the study was to compare multifocal extracapsular dissection with complete parotidectomy in the treatment of unilateral multifocal cystadenolymphomas of the parotid gland. MATERIALS AND METHODS: The records from all patients treated for unilateral multifocal cystadenolymphomas of the parotid gland at a tertiary referral center between 2000 and 2016 were retrospectively analyzed. RESULTS: 203 patients were included in the study. 96 patients were managed by multifocal extracapsular dissection, 107 patients underwent complete parotidectomy. Metachronous tumors were detected in 7 cases (3.4%) with a significant difference in the occurrence rate between multifocal extracapsular dissection (7/96, 7.3%) and complete parotidectomy (0/107, 0%) (p = 0.004). Permanent facial palsy was significantly more common after complete parotidectomy (21/107, 19.6%) than multifocal extracapsular dissection (2/96, 2.1%) (p = 0.000). CONCLUSIONS: The functional benefit of multifocal extracapsular dissection was counterbalanced by the advantage of complete parotidectomy, in terms of recurrences. Extracapsular dissection is at its limit in cases of multifocal cystadenolymphomas and the indication for it should be thoroughly verified in each and every case.
EVALuna2:35388